PENGARUH ROTASI AUDIT, AUDIT TENURE, DAN AUDIT FEE TERHADAP PENINGKATAN KUALITAS AUDIT PADA PERUSAHAAN MANUFAKTUR SEKTOR INDUSTRI BARANG KONSUMSI YANG TERDAFTAR DI BURSA EFEK INDONESIA - Sri Asyrafil Mustaqmah; Najma Fauziah (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2021)
The preservation of cultural heritage buildings is supported by documentation as reference data in maintenance efforts so that measurement and data presentation are required. Alternative presentation of three-dimensional data information for documenting cultural heritage buildings is expected to have a good dimension. The importance of documenting in the form of a three-dimensional model is due to the problem of referencing the shape to restore its original form rather than old building construction when damage occurs, especially collapsing due to earthquakes. One method that can be developed is photo-based three-dimensional documentation, namely by using cloaThis study aims to determine the effect of audit rotation, audit tenure, and audit fees on audit quality. This research uses purposive sampling method in sampling technique. The population used in this study is the entire manufacturing sector of the consumer goods industry listed on the Indonesia Stock Exchange in 2015-2019, while the research sample obtained is 13 companies after meeting the existing sample criteria. The data analysis technique used is SEM (Structural Equation Modeling) analysis technique based on PLS (Part Least Square) variance.The results showed that: 1) audit rotation had no significant effect on audit quality, 2) audit tenure had a significant effect on audit quality, 3) audit fees had a significant effect on audit quality. Keywords: Audit Rotation, Audit Tenure, Audit Fees, and Audit Quality.se-up photogrammetry techniques. Teristric photo known as Close Range Photogrammetry is a data acquisition technique using a camera located on the ground with a distance of less than 100 m. This research applies close range photogrammetry technique with a convergent method for the Panggung Krapyak cultural heritage building using a non-metric camera. Reference point (BM), binding point (GCP), detail sample point, and check point (ICP) are measured using a total station. 3D modeling is processed using Agisoft Photoscan Professional software automatically. The analysis process is carried out by comparing the dimensions of the 3D model results with the actual size in the field to show the value of the building geometry error. In this case, this is how close-up photogrammetric techniques can be an alternative in building documentation to present three-dimensional data information with good accuracy which is then used as reference data in long-term conservation monitoring activities and building reconstruction planning.The results of this study resulted in the number of points density 0,457 points / cm², 21.914 tie points, 3.395.055 dense point clouds, and 224.868 faces with a ground resolution accuracy of 0,37 cm / pix so that 1 pix has an actual value of 0,37 cm in the field and the dimensions of the 3D model produce an average difference in the distance of 0,0268 m and an average height difference of 0,0340 m. Based on the research that has been done, it is concluded that close-range photogrammetric techniques can be applied in documenting cultural heritage buildings as an alternative to presenting three-dimensional data information with good accuracy.